Catabolites of chlorophyll in senescing barley leaves are localized in the vacuoles of mesophyll cells - Matile, Philippe (1988)
Senescing barley leaves accumulate a series of pink pigments with the chemical properties of catabolites derived from chlorophyll. Levels of the major component of this group of pigments were quantified by HPLC and shown to be maximal in tissues exhibiting maximal rates of chlorophyll degradation. Protoplasts were isolated from senescent leaf tissue and fractionated to yield intact vacuoles and plastids. Although small but significant proportions both of total catabolites and of the dominant component of the series were recovered from the plastid fraction, the vast bulk of these compounds could be assigned to the vacuole. These observations suggest a role for the vacuole in the later stages of chlorophyll breakdown during senescence.